UTILIZATION OF POTATO WASTE FOR PRODUCTION OF BIOETHANOL: A NOVEL TECHNOLOGY - Kumar, Dharmendra (Potato Journal, 2022)
This study was conducted on the exploration of the potential use of potato as feedstock for bioethanolproduction, through saccharification and fermentation. The saccharification was performed via thermal and enzymatichydrolysis through the use of commercial enzymes such as cellulase, α-amylase, β-amylase and glucoamylosidase. Thepotato mash was mixed with 100 mL distilled water. The mixture was treated with different enzyme concentrations 10U, 15 U and 20 U. The mixture was incubated at the temperature of 75 °C and pH 5.0. The saccharification process wascompleted with 10 U of amyloglucosidase at 60 °C, pH 4.5 for 72 h. Samples were withdrawn at different time intervals andthe ethanol and consumed sugar assays were carried out by YSI Analyser. The use of commercial α-amylase led to higherreducing sugars release (69.21 ± 0.34 ± 0.32 g/100 g ) and in the combination of enzymes found the maximum efficiencyof saccharification i.e. 81.40 ± 0.56 g/100 g. The results showed that the enzymatic treatment led to higher saccharificationefficiency (81.40%) equivalent to 96% of the maximum theoretical. The fermentation process by using various strains ofYeast at different time intervals. The maximum ethanol yield was obtained by Saccharomyces cerevisiae MTCC 178 after72 h was 84.19 g/L.